Can Cash Conversion Cycle and Trade Credit Optimize Profitability? - Evi Apriliani; Wahyu Meiranto (Owner : Riset dan Jurnal Akuntansi, 2026)
The manufacturing sector is a cornerstone of Indonesia's economic development, yet persistent profitability fluctuations highlight ongoing difficulties in managing working capital efficiently. The Cash Conversion Cycle (CCC), Trade Credit Receivable (TCR), and Trade Credit Payable (TCP) are among the key financial indicators that significantly shape a firm's operational and financial outcomes. Accordingly, this study investigates how these three variables affect the profitability of manufacturing companies listed on the Indonesia Stock Exchange. A quantitative research design was adopted, employing panel data regression with a Fixed Effect model to control for firm-specific characteristics. The sample encompasses 196 companies with 784 total observations recorded between 2021 and 2024. Return on Assets (ROA) is used as the profitability measure, while CCC, TCR, and TCP function as the independent variables. The results demonstrate that CCC and TCP negatively and significantly affect profitability, indicating that extended cash cycles and heavy reliance on supplier credit can erode financial performance. In contrast, TCR shows a significant positive effect, suggesting that effective receivables management contributes to stronger revenue generation. Practically, the results indicate that a one-unit increase in CCC and TCP reduces ROA by 0.0000338 and 0.0277, respectively, whereas a one-unit improvement in TCR increases ROA by 0.2174. These findings collectively underscore the importance of efficient working capital management in manufacturing firms. By optimizing the cash conversion cycle and maintaining a well-balanced trade credit strategy, companies can meaningfully enhance their profitability and ensure long-term financial sustainability within Indonesia's competitive manufacturing landscape.